Ler para tocar versus ouvir para tocar: a realidade da Percepção na prática musical do músico popular e do músico de concerto - Silva, Mônica Michelly Lima da (2018)
This research seeks to understand the different ways of listening and perceiving within the musical reality, as well as to see the ways and advantages of developing the ability to read to play and to listen to play, emphasizing formal and informal teaching models, understanding how they can develop together, enabling a more fortified formation for the concert musician and the popular musician. In view of this, we seek to construct an object of study capable of healing some doubts that have always been present within the process of learning and studying perception and reading, as well as explaining the experience of some students who have already gone through this process of construction and hearing development or skill development with reading, reaching relative or absolute hearing as well as developing the ability to read quickly. In order to verify how the process of study and development of the perception and the musical reading happens, a survey was made within the bibliography of the area of the teaching of the perception and the cognitive psychology of the music, highlighting conclusions of authors like Otutumi (2013), Sloboda (2008), Sacks (2007), among others. A research was also carried out with some students of UFRN's technical and undergraduate course in music, also involving musicians who have been working in the labor market for many years, seeking to reflect and understand how the development of perception and reading happens in a way that help the student in his professional life through a gradual evolution. Keywords: Musical Education. Musical Perception. Hearing Training. Absolute Pitch.